PENERAPAN BERMAIN KASVO UNTUK MENINGKATKAN HASIL BELAJAR SERVIS BAWAH BOLA VOLI PADA SISWA KELAS IV SD NEGERI 1 PADAS KABUPATEN GROBOGAN TAHUN PELAJARAN 2012/2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
The purpose of this study was to determine the level of success through volleyball under serve application kasvo game in fourth grade student of Padas 1 state elementary school Grobogan regency Academic Year 2012/2013. This research is a classroom action research was conducted in two cycles. In two such cycles in each cycle consisting of four stages, namely planning phase, implementation phase, Observation phase and Reflection phase. The subjects in this study are all fourth grade students of Padas 1 state elementary school district Kedungjati Grobogan regency totaling 18 students, consisting of 4 sons and 14 daughters. Data analysis technique used is the percentage of service and instrument. From the results of the study in the first application of the material aspects of koqnitif reached 83%, 87% affective aspect , 77% psychomotor aspects, but the mastery learning students only reached 66.66% only. While in the second cycle of achievement aspect koqnitif reached 88%, reaching 87% afektiff aspect, psychomotor aspect reaches 79%, the percentage of student mastery have reached 89%. With the attainment of class classical completeness criteria of 85% then that action can be takenÂ  that Kasvo Application to Improve Learning result of Volleyball under Serve In Fourth Grade Students of Padas 1 state elementary school Grobogan regency Academic Year 2012/2013 can be declared a success.